知情同意臨床實踐中倫理學技術研究: Informed Consent as an Ethical Technique in Clinical Practice - CHENG, Guobin (International Journal of Chinese & Comparative Philosophy of Medicine, 2002)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 具體實踐中的知情同意是一種倫理學技術，注重利用現有的文化傳統、理論資源和法律工具，合理有效地分析問題、解決問題，強調它作為體現對病人基本權利的尊重和調節醫患關係手段的作用。在民主社會，知情同意乃是建立醫患權責餘的必要條件。知情同意來自於醫療活動的自發秩序：醫患雙方通過知情同意活動，明確醫療活動中雙方的權利和責任界限，進行有成效的醫療實踐。知情同意既是對基本人權的尊重，又是確保雙方責任的工具。具體實踐中的知情同意，提供一種促進多種價值觀和平共存、通過學習和對話實現平衡的運行機制，在社會整體利益優先與個人最基本權利不可侵犯的框架下滿足雙方不同的價值需求。臨床“知情同意”活動的目的在於：促進患者自主權的行使；明晰醫療活動中的權責關係，在合法限度內為醫療活動的正常進行提供保護。實踐中追求資訊的“充分”取決於患方要求的“主觀的充分”。臨床醫療活動中，醫方要不斷提高患方知情的充分程度。隨著知情程度的增加，患方自主程度隨之自動上升。目前關於“知情向意”的理論研究中，缺少對知情同意的狀況、分佈及相關因素的實地調查和量化分析，研究多集中在道德、文化理論上，實踐策略的指導意義不強。應當把知情同意視作貫穿於整個臨床醫療活動的一個連續的整體。要關注本社區成員的文化和心理結構的特殊性，從本社區歷史特點出發，建立本社區知情同意情況的常規模式和量化標準。還應當設計臨床知情同意調查制度，作為醫方制定知情同意策略的依據，同時又可作為說明醫療活動發生的真實過程的法律檔。 Informed consent is an ethical technique which emphasizes using the existing cultural traditions, theoretical resources and legal instruments to analyze and solve the problems reasonably and effectively. Informed consent can thus play a significant role in adjusting the relationship between patients and physicians. As an ethical technique, it focuses on the method of applying various ethical resources and not simply on the combination of the logical consequence and criteria. In a democratic society, informed consent is a necessary requirement for the right-duty relationship between patients and physicians. Informed consent is seen as a prerequisite obligation to physicians and implies certain rights for patients. Patients and physicians are bound by informed consent so that they are able to "trade" equally. Informed consent is not only a means to confirming the property rights but also a tool of reducing the costs of "trade". In practice, informed consent helps to promote and achieve the peaceful co-existence of pluralistic values. It can do so by learning and having conversations with the other sides so that different parties can satisfy under the framework which gives priority to the total interests of society and guarantees the fundamental rights of individuals. The aims of informed consent in clinical practice are to promote the self-determination of patients and to clarify rights and duties in medical activities. In practice, the sufficiency of information depends on the subjective sufficiency of patients. Physicians should ensure that the patient comprehend the information and follow the appropriate procedure to manage and supervise. The most active method for physician to take is to increase the degree of informational sufficiency. The degree of the patient’s self-determination increases accordingly with the increase of informational sufficiency. Their relationship can be described by a curve like "S". The current studies on informed consent in China lack the empirical data from field research. Most studies focus on the theoretical issues of morality and culture. As a result, research results are hardly applicable in clinical practice. Informed consent should a holistic entity in clinical practice. We should pay more attention to the specificity of the cultural and psychological structure of members of every community. We should establish the ordinary model and criteria of informed consent in the particular community. We should also design an applicable and legally-bond system of informed consent to regulate clinical practice. DOWNLOAD HISTORY | This article has been downloaded 13 times in Digital Commons before migrating into this platform.